Concurrent validity of the Vestibular/Ocular Motor Screening (VOMS) tool with the Dizziness Handicap Inventory (DHI) among adolescents with vestibular symptoms/impairment following concussion. (January 2022) - Eagle, Shawn R.; Feder, Abigail; Manderino, Lisa M.; Mucha, Anne; Holland, Cyndi L.; Collins, Michael W.; Kontos, Anthony P.
Abstract: Objective: To determine whether the Vestibular/Ocular Motor Screening (VOMS) tool demonstrates concurrent validity with the Dizziness Handicap Inventory (DHI) in a sample of concussed athletes referred for vestibular therapy and whether DHI items were predictive of VOMS outcomes. Design: Cross-sectional cohort study. Setting: Concussion specialty/vestibular therapy clinic. Methods: Adolescents (n = 55; 15.4 ± 1.6 years) with diagnosed sport-related concussion (SRC) with vestibular symptoms and/or impairment between October 2018–February 2020. Patients completed VOMS and DHI at initial visit. Seven individual VOMS and twenty-five DHI items, VOMS and DHI total score and three DHI sub-scales, were compared with Spearman correlations. Three backwards linear regression (LR) models were built to predict 1. VOMS vestibular symptoms, 2. VOMS ocular symptoms, and 3. near-point of convergence-distance (NPC-distance) using individual DHI items as predictors. Results: Spearman correlations ( p ) identified DHI items with moderate to strong associations for VOMS items. DHI sub-scales demonstrated moderate-to-strong correlations with VOMS items (p = 0.30–0.59). Total DHI score demonstrated a moderate-to-strong association with HSAC ( p  = 0.30), VSAC ( p  = 0.32), and SP ( p  = 0.61). Results from the LRs predicting VOMS ocular symptoms (R (Alsalaheen et al., 2010) = 0.56; p < 0.001), and VOMS vestibular symptoms (R (Alsalaheen et al., 2010) = 0.23; p = 0.01), and NPC-distance (R (Alsalaheen et al., 2010) = 0.56; p < 0.001) included significant DHI predictors. Conclusions: There was moderate-to-strong associations between VOMS and 56% of DHI items (i.e., p  > 0.30). Highlights: There was moderate-to-strong convergence between VOMS and 56% of DHI items. Certain DHI items were more related to VOMS: "does looking up increase your problem?". DHI could be augmented with items specific to impairments after concussion.